Developing a Rugby Book with Adapted Strategies and Training Methods Based on Local Wisdom for Elementary School Students - Septi Hariansyah; Irwandi; Zulheri Is; syahrianursaifi (Indonesian Journal of Sport Management, 2025)
Sports is one of the subjects taught and is very popular among students, especially at the elementary school level. Physical education at the elementary school level plays a crucial role in shaping character, motor skills, and instilling sportsmanship values ​​from an early age. Despite the development of these sports, many types of sports are still unknown to students. One of these is rugby, resulting in a low number of rugby players, especially in Aceh. This study aims to develop a digital rugby sports book that can be applied by elementary school students in their learning. The study was conducted using the Borg and Gall development method and the Culturally Responsive Teaching (CRT) approach. User validation and student responses were conducted at SD Negeri 18 Banda Aceh and SD Negeri Ateuk Aceh Besar. The results showed that the book is suitable as a teaching material for rugby learning in schools. The book received an average score of 88.5% from material experts, with very valid criteria. The book received a score of 93.6% from design experts and is in the very valid criteria with minor improvements. The average score of the book's assessment by teachers as users was 93% and is in the very suitable criteria for use in sports learning in schools. Overall, students' responses to the book received an average score of 90%. This concludes that the book is suitable and appropriate for use. This research demonstrates that the rugby sports book developed is suitable for use as teaching material in elementary schools.